"Analyzing Trends and Determinants of Female Labor Force Participation in Uttar Pradesh: A Gender and Regional Inequality Perspective " (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The research paper examines the complexities of women's engagement in the job market within India's most populous state. Through an analysis of data from the Periodic Labour Force Survey between 2014-15 and 2019-20, the study illuminates the evolving trends of female labour force participation, emphasizing gender disparities and regional nuances. Despite historical challenges such as traditional gender norms and limited educational opportunities, there is a promising trend of increasing female engagement, particularly in rural areas. However, urban regions still lag behind, indicating persistent disparities. By examining literature and empirical evidence, the study uncovers factors influencing women's workforce participation, including educational attainment, employment vulnerability, and social and religious influences. The findings underscore the importance of targeted interventions to promote women's inclusion, especially in urban settings, through initiatives focused on education, skill development, and entrepreneurship, ultimately aiming to bridge the gender gap and foster sustainable economic growth in Uttar Pradesh.